2018
DOI: 10.15406/jnhfe.2018.08.00283
|View full text |Cite
|
Sign up to set email alerts
|

Tenebrio molitor L., entomophagy and processing into ready to use therapeutic ingredients: a review

Abstract: The consumption of insects is known as entomophagy. Edible insects have been consumed for a long time in the traditional diets of many non-Western countries, but in recent times, the Food and Agriculture Organization of the United Nations (FAO) recognize them as having a high potential to treat malnutrition and food shortages without requiring large amounts of land or infrastructure. The larvae of Tenebrio Molitor L., the mealworm, have been processed to be as high in protein content as fish and meat. They are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Tenebrio molitor larva, as known as mealworm, appears to be a sustainable alternative protein source [ 14 ]. The mealworm is also rich in essential amino acids, polyunsaturated fatty acids, and a variety of vitamins and minerals, such as calcium, zinc, iron, magnesium, riboflavin, pantothenic acid, and biotin [ 15 , 16 , 17 ]. Previous studies reported that the Tenebrio molitor larvae possess pharmacological properties, such as anti-Alzheimer’s disease [ 18 ], anti-obesity [ 19 ], anticancer [ 20 ], anti-osteoporosis [ 21 ], anti-oxidation [ 22 ], and anti-inflammation activities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tenebrio molitor larva, as known as mealworm, appears to be a sustainable alternative protein source [ 14 ]. The mealworm is also rich in essential amino acids, polyunsaturated fatty acids, and a variety of vitamins and minerals, such as calcium, zinc, iron, magnesium, riboflavin, pantothenic acid, and biotin [ 15 , 16 , 17 ]. Previous studies reported that the Tenebrio molitor larvae possess pharmacological properties, such as anti-Alzheimer’s disease [ 18 ], anti-obesity [ 19 ], anticancer [ 20 ], anti-osteoporosis [ 21 ], anti-oxidation [ 22 ], and anti-inflammation activities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tenebrio molitor larva (mealworm) is a nutritious edible insect that provides essential amino acids, polyunsaturated fatty acids, trace elements, and vitamins ( Feng, 2018 ). Gessner et al (2019) reported that isonitrogenous substitution of 50% and 100% of casein with mealworm meal had lipid-lowering benefits in a hyperlipidemic rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Mealworm ( Tenebrio molitor larva), an edible insect, has attracted interest as a potential protein supplement because of its high content of beneficial nutrients, including essential amino acids, polyunsaturated fatty acids, trace elements, and vitamins [ 9 ]. Kim et al [ 10 ] have reported that mealworm protein hydrolysate prepared with alcalase and flavorzyme is easily digested and absorbed, and it has potential as a protein source for preventing sarcopenia.…”
Section: Introductionmentioning
confidence: 99%